Carcass Traits, Physicochemical Characteristics, Fatty Acid, and Protein Profile of Khiew Phalee, Pradu Hang Dam and Broiler Chicken Meat - Phromnoi, S.; Chumngoen, W.; Puangmalee, T.; Nuchchanart, W. (Tropical Animal Science Journal, 2025)
This study investigated the carcass traits, physicochemical characteristics, fatty acid profile and protein profile of male Khiew-Phalee native (KP), Pradu Hang Dam (PHD), and commercial broiler chickens (CBR). All samples were collected from farms in Uttaradit province and determined the carcass traits and physicochemical characteristics, including proximate composition, pH, meat color, shear force, drip loss, cooking loss, and also analyzed the fatty acid profile, purine content, and protein profile. The results showed that carcass traits such as live weight, carcass weight, and cutting percentage showed a highly significant decrease (p<0.01) in KP and PHD, except for the percentage of thigh, drumstick, and meat quality traits. There were highly significant differences in chemical composition, including moisture, protein, fat, ash and gross energy, lipid content, pH values, color values, drip loss, cooking loss, and shear force among the chicken breeds (p<0.01). The fatty acids significantly decreased in myristic acid, myristoleic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, and erucic acid in KP and PHD. Protein profile analysis found three different protein bands based on SDS-PAGE and LC-MS/MS analysis between three different chicken breeds, including 70 kDa proteins (heat shock 70 kDa and albumin OS) and 110 kDa protein (pyruvate kinase PKM) in KP and PHD with higher intensity than CBR. The cholesterol, purine, and uric acid of breast chicken meat were not affected by breed. Importantly, KP and PHD Thai native chickens possess lower amounts of unhealthy fatty acids, which positively affect the consumer and are anticipated to reduce the risk of many cardiovascular diseases.